Cognitive Behavior Therapy (CBT) Effectiveness in Overcoming Binge Eating Disorder (BED) in Adolescents - Frisca Putri Dorkas Wardani Sitompul (International Journal of Social Service and Research, 2022)
This study aims to see the effectiveness of Cognitive Behavior Therapy (CBT) in reducing binge eating disorder (BED) in adolescents. The research method used is an experimental study, namely a single experimental design in a home setting, where the subject is treated with CBT (Cognitive Behavior Therapy) techniques to overcome Binge Eating Disorder (BED). Data collection in this study used the methods of observation, interviews and psychological tests (DAP, BAUM, HTP, and SSCT). Data analysis in this study used an evaluation which was also continuously monitored using a monitoring table during the implementation of the intervention. Thus, the success of the CBT intervention was seen based on the achievement of the targets previously agreed upon by the subjects, especially in the Binge Eating Disorder (BED) eating disorder. The results showed that the intervention process in the form of cognitive behavior therapy (CBT) which was carried out for 10 days got satisfactory results. This is also consistent with the good prognosis of the subjects. Subjects were able to control their excessive appetite, and even changed their snacks to healthier foods, so as not to interfere with their health.